2017
DOI: 10.3945/cdn.117.001701
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dichotomous Indicator for Population-Level Assessment of Dietary Diversity in Women of Reproductive Age

Abstract: Background: Dietary diversity is a key element of diet quality, but diets of women of reproductive age (WRA; aged 15–49 y) in resource-poor settings are often deficient in a range of micronutrients. Previous work showed associations between simple food-group diversity indicators (FGIs) and micronutrient adequacy among WRA. For operational and advocacy purposes, however, there is strong demand for a dichotomous indicator reflecting an acceptable level of dietary diversity. Objective: The aim of the study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 27 publications
2
130
0
Order By: Relevance
“…Food items consumed were classified into 10 food groups according to recommended classifications (Food and Agriculture Organization [FAO] & Family Health International 360, ): (a) grains, white roots and tubers, and plantains (also known as starchy staples); (b) pulses (beans, peas, and lentils); (c) nuts and seeds; (d) dairy; (e) meat, poultry, and fish; (f) eggs; (g) dark green leafy vegetables; (h) other Vitamin A‐rich fruits and vegetables; (i) other fruits; and (j) other vegetables. The number of food groups consumed was summed up and dichotomised using a cut‐off at five food groups to compute the minimum dietary diversity for women (MDD‐W) indicator, which has been recently developed and validated as a proxy of micronutrient adequacy (FAO & Family Health International 360, ; Martin‐Prevel et al, ). We also used the number of food groups consumed as a continuous variable, namely the women's dietary diversity score (WDDS‐10), which ranged from 0 to 10 food groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food items consumed were classified into 10 food groups according to recommended classifications (Food and Agriculture Organization [FAO] & Family Health International 360, ): (a) grains, white roots and tubers, and plantains (also known as starchy staples); (b) pulses (beans, peas, and lentils); (c) nuts and seeds; (d) dairy; (e) meat, poultry, and fish; (f) eggs; (g) dark green leafy vegetables; (h) other Vitamin A‐rich fruits and vegetables; (i) other fruits; and (j) other vegetables. The number of food groups consumed was summed up and dichotomised using a cut‐off at five food groups to compute the minimum dietary diversity for women (MDD‐W) indicator, which has been recently developed and validated as a proxy of micronutrient adequacy (FAO & Family Health International 360, ; Martin‐Prevel et al, ). We also used the number of food groups consumed as a continuous variable, namely the women's dietary diversity score (WDDS‐10), which ranged from 0 to 10 food groups.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a randomised trial in Bangladesh showed that early multimicronutrient supplementation in pregnancy reduces the occurrence of stunting in boys during months 0-54, but not in girls (Khan et al, 2011). However, little attention has been paid to women's overall diet quality during preconception and gestation, particularly concerning dietary diversity, which has been shown to be associated with greater probability of micronutrient adequacy (Martin-Prevel et al, 2017). Poor dietary diversity during pregnancy has been documented in many contexts, particularly in low and middle-income countries (Lee, Talegawkar, Merialdi, & Caulfield, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin B12 intake was energy-adjusted [12]. The minimum dietary diversity for women (MDD-W) score was calculated using 24-h recalls and later on categorized into those with score less than 5 and those with 5 or more groups [13]. The MDD-W is a population-level assessment indicator of the proportion of women (15-49 years) who consume a diet containing 5 or more food groups, which can be used as a proxy indicator of higher micronutrient adequacy [13].…”
Section: Data Collectionmentioning
confidence: 99%
“…The mean minimum dietary diversity for women (MDD-W) score during pregnancy was 2.86 (SD = 2.66). Only 6 (1.3%) of the women assessed had a mean score of MDD-W of at least 5 food groups, which is the FAO definition of minimum dietary diversity [13]. The median vitamin B12 intake was above the recommended dietary allowance (RDA) of 2.8 µg/d for lactating women in the multivitamin and placebo groups [15].…”
Section: Study Participantsmentioning
confidence: 99%
“…Widely agreed upon as an indicator for assessing diet diversity – a vital element of diet quality – the MDD-W is a dichotomous indicator that classifies women as having a high- or low-diet diversity based on the number of food groups consumed over 24 h [36]. Though unanimously endorsed by academia, international research institutes, the UN and donor agencies during its introduction in 2014 [37], the MDD-W remains underutilized in both government-led and independent assessments of nutrition and health [38]. Rigorous nutrition studies that use the MDD-W as a primary indicator or in tandem with biomarkers and other nutrition indicators are urgently needed to raise this metric’s visibility and application.…”
Section: The Role Of Nutrition Scientistsmentioning
confidence: 99%